2023
DOI: 10.1186/s12916-023-02952-1
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of COVID-19 on structural changes in specific brain regions: a Mendelian randomization study

Abstract: Background Previous studies have found a correlation between coronavirus disease 2019 (COVID-19) and changes in brain structure and cognitive function, but it remains unclear whether COVID-19 causes brain structural changes and which specific brain regions are affected. Herein, we conducted a Mendelian randomization (MR) study to investigate this causal relationship and to identify specific brain regions vulnerable to COVID-19. Methods Genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…Long-term changes in resting-state amplitude of low-frequency fluctuation (ALFF) were also reported for these areas in patients one year after recovery (16). Furthermore, the caudal middle frontal gyrus, exhibiting increased DBSI-HF in our study, has been linked to SARS-CoV-2-induced structural changes such as reduced cortical thickness (93). Interestingly, this COVID-19-related structural alteration within this brain region was further associated with increased inflammation markers in the cerebrospinal fluid (94).…”
Section: Significant and Nominal Associations Of Dbsi-hf With Covid-19supporting
confidence: 71%
“…Long-term changes in resting-state amplitude of low-frequency fluctuation (ALFF) were also reported for these areas in patients one year after recovery (16). Furthermore, the caudal middle frontal gyrus, exhibiting increased DBSI-HF in our study, has been linked to SARS-CoV-2-induced structural changes such as reduced cortical thickness (93). Interestingly, this COVID-19-related structural alteration within this brain region was further associated with increased inflammation markers in the cerebrospinal fluid (94).…”
Section: Significant and Nominal Associations Of Dbsi-hf With Covid-19supporting
confidence: 71%
“…Long-term changes in resting-state amplitude of low-frequency fluctuation (ALFF) were also reported for these areas in patients one year after recovery ( Du et al, 2022 ). Furthermore, the caudal middle frontal gyrus, exhibiting increased DBSI-HF in our study, has been linked to SARS-CoV-2-induced structural changes such as reduced cortical thickness ( Zhou et al, 2023 ). Interestingly, this COVID-19-related structural alteration within this brain region was further associated with increased inflammation markers in the cerebrospinal fluid ( Sanabria-Diaz et al, 2022 ).…”
Section: Discussionmentioning
confidence: 68%
“… 52 Our findings align with a recent Mendelian randomization study that suggested a nominal association between the severe COVID-19 phenotype and reduced cortical surface area in the superior parietal gyrus, pericalcarine and parahippocampal gyrus. 53 Taken together, these evidences indicated that the superior parietal gyrus may be vulnerable to COVID-19 infection, but the precise mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%